Review Article: The Impact of Doctor–Pharma Relationships on Prescribing Practice - Asif, Imran; Amin, Shehzad (Journal of Basic & Applied Sciences, 2012)
Pharmaceutical industry is one of the major manufacturing industries in Pakistan going hand in hand with medical profession providing value-added healthcare medicines to the ailing humanity. The industry is, however, facing a number of challenges, which are creating hurdles in the way of its professional advancement, especially in the application of a model based on ethics. Ethics has been a major focus of debate in today’s world because of the declining trend of ethical values and social responsibility in healthcare profession. The International Federation of Pharmaceutical Manufacturers Association (IFPMA) defines the code of ethics as: “Ethics should be a part of any business, particularly a business which is dealing with human life” [1-2].This highlights an important aspect of relationship between doctors and the pharmaceutical industry and its consequences for the prescribing pattern of physicians. We have conducted a research which is confined to doctors, chemists and companies. The survey on doctors has revealed that most of the doctors have agreed that the patient-doctor counseling is the most important aspect of ethical medical practice, followed by quality care and patients’ affordability to purchase medicines and rationale use of medications. Most of the physicians believe that unethical behavior starts from the doorsteps of drug-manufacturing companies and is followed by non-qualified persons or quacks and some doctors as well. A number of doctors are of the opinion that factors such as entertainment activities with families, frequent offers of lunch and dinners and product samples influence the prescribing behavior of medications. The survey on drugs companies shows that a major portion of the promotional budget is spent on advertisement and promotion of products and customers’ obligation, which force the doctors to prescribe their products. During the survey when we asked chemists about the trend of prescription of medicines, they pointed out that majority of the patients came to them without any doctor’s prescription. This indicates the domination of drugs companies which are spending the huge money on the promotion of their products and compelling the people to purchase medicines without any prescription. Besides this, a high margin of profit is offered to the doctors as well as the chemists by the drugs companies in an attempt to woo them to replace cheap medicines with the expensive ones they sell in the market.